2009
DOI: 10.1007/s00401-009-0485-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of β-amyloid deposits in human brain: a study of the BrainNet Europe Consortium

Abstract: β-Amyloid (Aβ) related pathology shows a range of lesions which differ both qualitatively and quantitatively. Pathologists, to date, mainly focused on the assessment of both of these aspects but attempts to correlate the findings with clinical phenotypes are not convincing. It has been recently proposed in the same way as ι and α synuclein related lesions, also Aβ related pathology may follow a temporal evolution, i.e. distinct phases, characterized by a step-wise involvement of different brain-regions. Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
107
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 153 publications
(114 citation statements)
references
References 31 publications
4
107
1
Order By: Relevance
“…The predominantly parieto-occipital location of the WMH further supports the hypothesis that they relate to CAA. CAA, which is present to at least some degree in 70%e100% of AD brains at postmortem (Bergeron et al, 1987;Ellis et al, 1996), has a particular predilection for the occipital lobes (Alafuzoff et al, 2009;Thal et al, 2002), and a posterior distribution of WMH has been shown to predict pathologically confirmed CAA (Thanprasertsuk et al, 2014). Although only one of the APP subjects had a mutation within the Ab coding domain, their ARWMC score was considerably higher than the median for the APP group, consistent with pathological reports of severe CAA in cases with intradomain APP mutations.…”
Section: Discussionmentioning
confidence: 98%
“…The predominantly parieto-occipital location of the WMH further supports the hypothesis that they relate to CAA. CAA, which is present to at least some degree in 70%e100% of AD brains at postmortem (Bergeron et al, 1987;Ellis et al, 1996), has a particular predilection for the occipital lobes (Alafuzoff et al, 2009;Thal et al, 2002), and a posterior distribution of WMH has been shown to predict pathologically confirmed CAA (Thanprasertsuk et al, 2014). Although only one of the APP subjects had a mutation within the Ab coding domain, their ARWMC score was considerably higher than the median for the APP group, consistent with pathological reports of severe CAA in cases with intradomain APP mutations.…”
Section: Discussionmentioning
confidence: 98%
“…Future studies should also aim to re-evaluate these observations to validate this approach and to develop a concise classification of ARTAG for diagnostic neuropathology. To reach this goal, paradigms will need to be designed for ARTAG along the lines used to standardize evaluation and diagnostic criteria for tau, amyloid and α-synuclein and other major pathologies [24, 10, 45]. Subsequently, it will be possible to evaluate inter-rater reliability of the proposed evaluation and eventually to merge clinical and pathologic data from multiple centers to determine practical significance of ARTAG.…”
Section: Discussionmentioning
confidence: 99%
“…For AD, the criteria of Braak were used modified for thin sections 17 and vascular amyloid ␤ deposits were assessed according to BrainNet Europe (BNE) instructions. 18 For FTLD, the Cairns classification was used. 19 For DLB, the Braak criteria were used 20 modified according to the BNE instructions.…”
mentioning
confidence: 99%